DETERMINATION OF SUN PROTECTION FACTOR (SPF) VALUE IN LIME (CITRUS AURANTIFOLIA) PEEL EXTRACT USING UV-VIS SPECTROPHOTOMETRY METHOD - AM Andy Suryadi; Mahdalena SY Pakaya; Endah Nurrohwinta Djuwarno; Julianty Akuba (Jambura Journal of Health Sciences and Research, 2021)
Lime (Citrus aurantifolia) is a plant that contains phenolic compounds, such as phenols, flavonoids, and tannins. With this content, lime peel extract has the potential as a sunscreen and has antioxidant activity. Sunscreen compounds refer to ones that can protect the skin from the effect of ultraviolet radiation. At first, the peel was extracted by maceration method using three solvents with different polarity (n-hexane, ethyl acetate, and 70% ethanol). The preliminary test found that the ethyl acetate and ethanol 70% extracts positively contained phenol, tannin, and flavonoid compounds, which were marked by a color change in the sample and continued to test the sunscreen activity. Further, the sunscreen activity test was determined based on the determination of the Sun Protection Factor (SPF) value that was done at 290-320 nm (wavelength) with a 5 nm interval.  The results showed that the sunscreen activity of the peel extract is very good at a concentration of 200 ppm for ethyl acetate extract with a value of 28.8; meanwhile, ethanol extracts 70% and ethyl acetate extracts of 400 and 600 ppm concentrations with an average SPF value of 24, 42.5, 42.2 and 81.8, respectively, are included in ultra protection because they have an SPF value of 15.